2005
DOI: 10.1007/s11224-005-8254-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Chemical Calculation Studies on 4-Phenyl-1-(Propan-2-Ylidene)Thiosemicarbazide

Abstract: Ab initio calculations of the structure, atomic charges, natural bond orbital, and thermodynamic functions have been performed at HF/6-311G * * and B3LYP/6-311G * * levels of theory for the title compound of 4-phenyl-1-(propan-2-ylidene)thiosemicarbazide. The calculated results show that the sulfur atom and all of the nitrogen atoms have bigger negative charges and they are the potential sites to react with the metallic ions, which make the title compound become a multidentate ligand. The coordination ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
36
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(43 citation statements)
references
References 30 publications
7
36
0
Order By: Relevance
“…The result in the differences of bond parameters between the calculated and experimental values depend on the existence of the crystal field along with the inter-molecular interactions connects the molecules together in the solid state. 34 The calculated geometric parameters by using the B3LYP/6-31G(d) method are in good agreement with the X-ray structure, in spite of the observed differences, in general.…”
supporting
confidence: 57%
“…The result in the differences of bond parameters between the calculated and experimental values depend on the existence of the crystal field along with the inter-molecular interactions connects the molecules together in the solid state. 34 The calculated geometric parameters by using the B3LYP/6-31G(d) method are in good agreement with the X-ray structure, in spite of the observed differences, in general.…”
supporting
confidence: 57%
“…We note that the experimental results are for the solid phase and the theoretical calculations are for the gas phase. In the solid state, the existence of a crystal field along with the intermolecular interactions connect the molecules together, which results in the difference in bond parameters between the calculated and experimental values 28 .…”
Section: Dft Calculationsmentioning
confidence: 99%
“…Theoretical studies can further advance the understanding of the molecular properties of TSC compounds and their complexes with transitional metals, and a few such studies have been recently reported [36][37][38][39][40][41]. Some studies have focused on optimized geometries and conformational distribution [37,38] while others have focused mainly on their NMR properties [39][40][41].…”
Section: 'mentioning
confidence: 99%
“…Some studies have focused on optimized geometries and conformational distribution [37,38] while others have focused mainly on their NMR properties [39][40][41]. We recently reported the results of a hybrid density functional theory investigation of a series of alloxan-based thiosemicarbazones and semicarbazones [42].…”
Section: 'mentioning
confidence: 99%